PENDIDIKAN AGAMA KRISTEN KELUARGA ANTARA HARAPAN ORANG TUA DAN DUNIA PSIKOLOGIS ANAK - Agripka Susanti Imelda Punuf; Friga Ayudina Asanab; Frigen Rinaldy Lay; Jefri Edduar Ottu; Harley Sandra Taebenu (CV. Adiba Aisha Amira, 2026)
Christian religious education in the family is one of the main foundations in shaping children’s faith and character. However, in reality, there is often tension between the expectations of Christian parents and the psychological reality of children. On the one hand, many parents expect their children to be obedient, diligent in worship, and behave in accordance with Christian values. On the other hand, children are in a stage of psychological development that requires acceptance, emotional support, and even a sense of security for the children themselves. This study aims to analyze the dynamics of Christian faith education in family life, highlighting the tension that occurs between parental expectations and the psychological condition of children, and offering a balanced, sustainable, and humanistic approach to Family PAK. The method used was qualitative, using a literature study approach to various scientific literature related to Family Religious Education and Child Development Psychology. The results of the study showed that religious education that is too authoritarian or normative in children’s daily lives has the potential to make children less creative and raise them in a rigid pattern so that sometimes children are less able to express themselves freely. Therefore, Christian Religious Education in the family needs to reinterpret and integrate Christian faith with an understanding of child psychology so that the process of shaping a child’s faith can take place in a holistic, relational, and sustainable manner and fulfill the objectives of Family Religious Education